Study of Suitability and Carriying Capacity on Ecotourism of Turtle Conservation in The Tikus Island Bengkulu City - Dede Hartono; Zamdial Zamdial; Musriyadi Nabiu; Ari Anggoro; Ridka Rizki Novanda; Dwi Bulan Dari Julian Futri (JURNAL ENGGANO, 2023)
Tikus Island is the only small island located very close to Bengkulu City. Tikus island has long been known by the Bengkulu people as a turtle nesting area. The types of turtles found were hawksbill and green turtles. In recent years, research has shown that the turtle population has decreased, which is thought to be caused by the degradation of environmental conditions. Recently, environmentalists have plans to revitalize Tikus Island. Tikus Island has a very vital economic function and environmental function for the people of Bengkulu City. The Marine Edu-park development plan is one of the efforts to revitalize Tikus Island with an integrated development concept. Integration between environmental and economic sectors, as well as regional development integration between Tikus Island and the surrounding tourism locations in Panjang Beach, Bengkulu City. In this study, the plan for the development of turtle conservation ecotourism on Tikus Island, will be analyzed based on the environmental conditions of the island and in the surrounding Water Conservation Area (KKPD P Tikus). The purpose of this study was to determine the suitability value and carrying capacity of turtle ecotourism in the Tikus Island area, Bengkulu City. This study uses a survey method to data collection with using observation and interviews. The types of data used are primary data and secondary data. Suitability analysis is the determination of the value of Tikus island that is suitable for ecotourism activities. Carrying capacity functions as a limitation of activities carried out by humans in an environment. The results of this study indicate that the Turtle Ecotourism Conformity Index (IKEP) of Tikus island is in the very appropriate category (S1). The carrying capacity is 60 people/day with 5 visits every day. Key words : suitability, carrying capacity , ecotourism, turtles.